Coming out on the mantle of pioneers! (Journal of the College of Basic Education, 2022)
No one interested in literature affairs can deny the great poetic achievement achieved by the pioneers (Al-Sayyab and Nazek Al-Malaika) and their rich contribution in supporting the new poetic movement and their creative influence on successive generations of poets.